2007
DOI: 10.1002/eji.200737604
|View full text |Cite
|
Sign up to set email alerts
|

Genomic variants of TLR1 – It takes (TLR‐)two to tango

Abstract: Toll-like receptors (TLR) are innate immune sensors of microbial cell wall products that initiate early host responses. The TLR2 receptor complex has been shown to contain heterodimers of TLR2 with either TLR1 or TLR6 enabling the host to detect different microbial molecules, such as lipopeptides of different chemical composition. In this issue of the European Journal of Immunology, an important role in the sensing of microbial products for I602S, a single nucleotide polymorphism (SNP) in human TLR1 has been i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 24 publications
3
25
0
Order By: Relevance
“…To further investigate TLR expression in T cell subsets, we performed real-time RT-PCR on Th1, Th2, and Th17 subsets using bone marrow-derived macrophages and RFP + γδ T cells from IL-17F-RFP reporter mice as positive controls. It has previously been shown that TLR2 signaling requires heterodimerization with TLR1 or TLR6 (Schumann and Tapping, 2007). In accordance, TLR1, 2, and 6 mRNAs were expressed to the highest degree in Th17 cells compared to Th1 and Th2 subsets (Figure 1A and Figure S1A available online).…”
Section: Resultsmentioning
confidence: 99%
“…To further investigate TLR expression in T cell subsets, we performed real-time RT-PCR on Th1, Th2, and Th17 subsets using bone marrow-derived macrophages and RFP + γδ T cells from IL-17F-RFP reporter mice as positive controls. It has previously been shown that TLR2 signaling requires heterodimerization with TLR1 or TLR6 (Schumann and Tapping, 2007). In accordance, TLR1, 2, and 6 mRNAs were expressed to the highest degree in Th17 cells compared to Th1 and Th2 subsets (Figure 1A and Figure S1A available online).…”
Section: Resultsmentioning
confidence: 99%
“…TLR2, unlike the other TLRs, functions as a heterodimer forming either a TLR2/TRL1 or TLR2/TLR6 complex, allowing TLR2 to discriminate between different types of ligands [29], [30]. TLR2/TLR1 heterodimers bind triacylated lipoproteins (e.g., Pam3CSK4 and lipomannan [LM]) while TLR2/TLR6 heterodimers bind diacylated lipoproteins (Pam2CSK4, lipoteichoic acid [LTA]) [31][33]. We tested if CEP potentiated signaling from either TLR2/TLR1, TLR2/TLR6, or both by co-stimulating BMDMs with CEP-BSA and either Pam3CSK4, LM, Pam2CSK4, or LTA.…”
Section: Resultsmentioning
confidence: 99%
“…Some of these changes may be caused by the presence of a SNP in the coding region of the protein. The effects of SNPs on the structure of proteins and the consequent effect on TLR signaling have been described in many studies (32)(33)(34)(35).…”
Section: Discussionmentioning
confidence: 99%